Hemodynamic trajectories and outcomes in patients with pulmonary arterial hypertension. (December 2020) - Amsallem, Myriam; Bagherzadeh, Shadi P.; Boulate, David; Sweatt, Andrew J.; Kudelko, Kristina T.; Sung, Yon K.; Feinstein, Jeffrey A.; Fadel, Elie; Mercier, Olaf; Denault, Andre; Haddad, Francois; Zamanian, Roham
The relative pulmonary to systemic pressure ratio (mean pulmonary arterial pressure/mean arterial pressure) has been proven to be valuable in cardiac surgery. Little is known on the prognostic value of baseline and trajectory of mean pulmonary arterial pressure/mean arterial pressure in pulmonary arterial hypertension. Patients with confirmed idiopathic, familial, drug and toxins, or connective tissue disease-related pulmonary arterial hypertension and at least one complete right heart catheterization were included and prospectively followed-up for 5.9 ± 4.03 years. Correlates of the primary end point (i.e. death or lung transplant need) during follow-up were determined using Cox regression modeling. Results showed that among the 308 patients included, 187 had at least one follow-up catheterization (median time between catheterizations: 2.16 (1.16–3.19) years). In the total cohort (mean age 47.3 ± 14.9 years, 82.8% of female and 58.1% in New York Heart Association class 3 or 4), mean pulmonary arterial pressure/mean arterial pressure (1.38 (1.07–1.77)) was associated with outcome ( p  = 0.01). Mean pulmonary arterial pressure/mean arterial pressure was incremental to a basic model (including right atrial pressure, systolic blood pressure, New York Heart Association class 3 or 4, and connective tissue disease) for outcome prediction, while mean pulmonary arterial pressure was not. In the 187 patients with a follow-up catheterization, both delta mean pulmonary arterial pressure and delta mean pulmonary arterial pressure/mean arterial pressure were associated with outcome (1.32 (1.11–1.58) and 1.31 (1.1–1.57) respectively, p  < 0.01). Mean pulmonary arterial pressure and mean pulmonary arterial pressure/mean arterial pressure were both incremental to the basic model, while worsening in mean pulmonary arterial pressure or mean pulmonary arterial pressure/mean arterial pressure did not reach significance. In conclusion, mean pulmonary arterial pressure/mean arterial pressure at baseline prognosticates long-term outcome with a significant, albeit modest, incremental value to basic variables.